Pengaruh Hasil Belajar Dasar Listrik dan Elektronika, Motivasi, dan Kesiapan Siswa terhadap Hasil Praktik Kerja Industri: - Roga Dinar Prabustya; Mohammad Fatkhurrokhman; Ilham Akbar Dharmawan (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research is a type of quantitative research that aims to determine whether there is an effect of practical learning outcomes, student motivation and student readiness on the results of industrial work practices for students in the Electrical Power class SMKN 2 Serang City and how big the effect is. The research method used is quantitative research which consists of 4 variables, namely Basic Electrical and Electronics Learning Outcomes (X1), Learning Motivation (X2), Student Readiness (X3), Industrial Work Practice Results (Y). The data were taken using questionnaires, tests, and final grades of students which were then processed using the SPSS data analysis application. The results of the study show that there is no effect between basic electrical and electronic learning outcomes on industrial work practice results with a value of sig (0.279 > 0.05), student learning motivation has an influence on students' industrial work practice results with a value of sig (0.026 < 0.05), student readiness has an influence on the results of industrial work practices with a sig value (0.045 < 0.05). Based on the results of the analysis showed that the basic learning outcomes of electricity and electronics, learning motivation and student readiness had an effect of 0.071 or 7.1% unit. Keywords: The Influence Of Electricity And Electronics Basic Learning Outcomes, Students' Motivation, And Readiness On Industrial Work Practice Outcomes